A Note on Comparative Costs - Burns, Arthur F. (Quarterly Journal of Economics, 1928)
Journal Article A Note on Comparative Costs Get access Arthur F. Burns Arthur F. Burns Rutgers University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 42, Issue 3, May 1928, Pages 495–500, https://doi.org/10.2307/1884789 Published: 01 May 1928